PSYCHOLOGICAL CHARACTERISTICS OF DEVELOPING VOLITIONAL QUALITIES IN ADOLESCENTS (International Conference on Economics, Finance, Banking and Management, 2025)
The article explores the psychological characteristics of developing volitional qualities in adolescents. Special attention is paid to the role of motivation, emotional regulation, and self-control in the formation of willpower. The study highlights the influence of family, school, and peer groups on the development of volitional traits such as perseverance, determination, responsibility, and goal orientation. Practical recommendations are provided for educators and psychologists to strengthen adolescents’ volitional qualities and support their personal growth.